Perceptions of Afghanistan Students on the Use of Online Tools for Learning - Hafizoah, Kassim; Bakhtyari, Mohammad Basir (Global Research & Development Services, 2014)
Online technology plays a significant role in higher education especially in assisting teaching and learning. In Afghanistan, to move towards student-centered and technology-driven learning, the Ministry of Higher Education (MoHE) encourages all universities to use technology to facilitate teaching and learning. This study, therefore, attempts to measure Afghanistan university students’ perceptions of online tools utilization on their learning. A survey questionnaire was distributed to 217 students, and 35 of them volunteered to be interviewed. The results generally indicated positive perceptions of online tools utilization. However, participants believed that online tools are able to assist them develop surface learning better than deep learning. This is due to a number of barriers faced by the students, and universities in providing better learning experiences through technology. The findings suggest a need for trainings and constant exposure for both teachers and students for online tools to be effectively utilized to enhance learning.